(untitled) (MAUSAM, 1990)
A 40 wave 121ayer global spectral model based on diabatic primitive equations in spherical coordinates has been integrated for a 23-dayperiod starting with the initial fields of 12 GMT of 15 December 1986. Results of verification of model outputs, following the procedure laid down by WMO, are presented in this study. Model verification statistics have been computed for the global regime as well as the Indian window (45° E-120° E, 15 S-55° N). It is found that uninitialised analysis and forecast are well correlated for a period up to 5 days for both the global domain and the Indian window.